(untitled) (Historia, 2021)
On the 1st of January 1876 the first sod of the Natal railways was turned at Durban by the Lieutanant Governor, Sir Henry Bulwer. The system that was thus started was to consist of a main line from Durban to Pietermaritzburg with branch lines along the coast to Verulam and Isipingo respectively. Extensions of the main line were subsequently authorised so that a continuous process of construction proceeded until 1895 when the connection between Durban and the Witwatersrand was completed. In the construction of this rail link of 776 kilometres - the biggest public work undertaken by the colony in the 19th century - a large labour force was needed. The aim of this article is to show that the railway department came to rely chiefly on Indian labour and in fact became the biggest single employer of Indian labour in Natal in the 1880’s and 1890’s. Attention will also be given to the control and treatment of this large labour contingent.